(Early Childhood Creativity: A Psychoanalytic Theory Perspective and Its Implications in Education) - Khalqi, Khairul; Akbar, Feri (JUPE : Jurnal Pendidikan Mandala, 2025)
The preparation of this article the author describes the various basic concepts of creativity, views about early childhood, psychoanalysis and the figures included in it, as well as the implications of the view of psychoanalysis for education at an early age. The method used is library research, which compares the results of various types of readings related to the research conducted. The results in this study are psychoanalytic theorists see creativity as the result of overcoming a problem that usually begins in childhood. The creative person is seen as someone who has had a traumatic experience, which is confronted by allowing conscious and unconscious ideas to be mixed into innovative solutions from trauma. Creative actions transform unhealthy psychological states into healthy ones. From the view of the psychoanalytic theory of the theory of creativity, of course, it is very visible at the time of the children themselves. Creativity in children who are referred to as personality is very important and certainly needs to be developed maximally in the world of education. Even more so when children are momentum to develop the greatest potential for children's creativity development. The role of educators at an early age will certainly affect his personality until the child is an adult..